Improving Access to Home and Community Care: An Analysis of the 2017 Health Accord - Rhiannon Roberts; Mary Bartram; Katerina Kalenteridis; Amélie Quesnel-Vallée (McMaster University Library Press, 2021)
In 2017, the federal Liberal government confirmed the new Canadian Health Accord, which included a targeted transfer of $6B over ten years to the provinces and territories to improve access to home and community care services. Although there were previous federal initiatives aimed at enhancing home and community care services, challenges remain. Many Canadians cannot access home care, and a high burden of care is placed on formal and informal caregivers. These challenges partly stem from an unregulated home care sector and a societal undervaluing of the caregiving role. In 2016, federal, provincial, and territorial governments met and established home and community care as a Canadian health priority. Funding was agreed to in principle from 2016 to 2017 and finalized from 2017 to 2019 through a series of bilateral agreements. The targeted transfer appears to be boosting investments in the home care sector and fostering collaboration across jurisdictions. However, it is unclear whether there have been improvements in access to home and community care.